Tritium ( 3 H) Retention In Mice: Administered As HTO, DTO or as 3 H-Labeled Amino-Acids. Issue 5 (May 2017) - Priest, Nicholas D.; Blimkie, Melinda S.J.; Wyatt, Heather; Bugden, Michelle; Bannister, Laura A.; Gueguen, Yann; Jourdain, Jean-Rene; Klokov, Dmitry
Abstract : Abstract: The objective of this study was to compare the biokinetics of injected 3 H-labeled light (HTO) and heavy (DTO) water in CBA/CaJ mice and to compare the organ distribution and/or body content of 3 H administered by chronic ingestion for 1 mo to C57Bl/6J mice, as either 3 H-labeled water or 3 H-labeled amino acids (glycine, alanine and proline). HTO and DTO were administered to CBA/CaJ mice by single intraperitoneal injection and body retention was determined for up to 384 h post-injection. Tritium-labeled water or 3 H-labeled amino acids were given to C57Bl/6J mice ad libitum for 30 d in drinking water. Body content and organ distribution of 3 H during the period of administration and subsequent to administration was determined by liquid scintillation counting. No differences were found between the biokinetics of HTO and DTO, indicating that data generated using HTO can be used to help assess the consequences of 3 H releases from heavy water reactors. The results for 3 H-water showed that the concentration of radionuclide in the mice reached a peak after about 10 d and dropped rapidly after the cessation of 3 H administration. The maximum concentration reached was only 50% of that in the water consumed, indicating that mice receive a significant fraction of their water from respiration. Contrary to the findings of others, the pattern of 3 H retention following the administration of a cocktail of the labeled amino acids was very little different from that found for the water. This is consistent with the suggestion that most of the ingested amino acids were rapidly metabolized, releasing water and carbon dioxide.